2005 IEEE Engineering in Medicine and Biology 27th Annual Conference 2005
DOI: 10.1109/iembs.2005.1615656
|View full text |Cite
|
Sign up to set email alerts
|

Prosthetic Visual Acuity in Irregular Phosphene Arrays Under Two Down-Sampling Schemes: A Simulation Study

Abstract: To investigate the effects of phosphene array irregularity in visual prostheses, a model of phosphenes' positional uncertainty was devised and two different image down-sampling schemes, adapting and non-adapting, were proposed. Based on a simulation system, visual acuity tests were given to four normally sighted subjects under seven degrees of array irregularity and the two down-sampling schemes. With the irregularity index increasing from 0 to 0.6, visual acuity fell over a range of 0.22 logMAR (logarithm of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Cha et al [11] suggested that under such circumstances subjects directed their gaze so as to 'choose' the best viewing position in order to identify the orientation of the Snellen E, thus improving visual acuity scores. With irregular phosphene matrices, Cai et al [12] noted that subjects learned to select areas with denser phosphenes for scanning in order to maximize the spatial frequency content of the stimuli, supporting the self-directed maximization hypothesis. Head movements also allowed subjects to expand their effective fields of view and rudimentary depth perception through parallax [13].…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Cha et al [11] suggested that under such circumstances subjects directed their gaze so as to 'choose' the best viewing position in order to identify the orientation of the Snellen E, thus improving visual acuity scores. With irregular phosphene matrices, Cai et al [12] noted that subjects learned to select areas with denser phosphenes for scanning in order to maximize the spatial frequency content of the stimuli, supporting the self-directed maximization hypothesis. Head movements also allowed subjects to expand their effective fields of view and rudimentary depth perception through parallax [13].…”
Section: Introductionmentioning
confidence: 93%
“…Furthermore, though a static image of phosphenes may simply appear like discrete dots, when relative movement is induced via scanning, a more coherent structure of the stimulus emerges. The existing literature on simulated prosthetic vision tends to attribute this to visual memory and mental imagery [12,[14][15][16][17][18][19], filling-in the lack of visual information in the gaps between the discrete phosphenes by accumulating the visual information through temporal integration. This is believed to subserve the identification of spatial details beyond the sampling-theoretic limit [20] of the phosphene matrix [12,14,17,21].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Contemporary artificial vision devices are based on inducing small, discrete visual percepts, called phosphenes, generated with electrical stimulation12345678. Users of these devices face the task of grouping collections of discrete elements into perceptual wholes to recognize visual content.…”
mentioning
confidence: 99%